INDUCTION OF NUCLEAR ENVELOPES AROUND METAPHASE CHROMOSOMES AFTER FUSION WITH INTERPHASE CELLS - Ikeuchi, Tatsuro (The Rockefeller University Press, 1971)
The process of cellular fusion induced by Sendai virus in Chinese hamster cells (Don line) afforded us the opportunity to study nuclear envelope formation around metaphase sets in the presence of interphase nuclei, when chromosome pulverization failed to occur in such multinucleate cells. Morphologically, the enveloped metaphase chromosomes resembled a normal telophase nucleus, though minor differences prompted us to call it telophase-like. Electron microscopic observations demonstrated that the membranes enveloping the chromosomes appeared to be identical with a normal nuclear envelope. The longer the cells were incubated with Colcemid before fusion, the higher was the number of cells with telophase-like nuclei and the lower the percentage of cells with pulverizations. Furthermore, the number of pulverizations bore a somewhat direct relationship to the ratio of metaphase to interphase nuclei in multinucleate cells, and the number of telophase-like nuclei was inversely proportional to this ratio. A hypothesis is advanced in which a balance between the activities of a chromosome pulverization factor and a nuclear envelope formation factor, the former in metaphase cells and the latter in interphase cells, is decisive as to the nature of morphologic events observed in virus-induced fused cells.